ANALISIS INDEKS KEPUASAN MASYARAKAT (IKM) TERHADAP PELAYANAN PUBLIK DI KANTOR KECAMATAN SIPORA UTARA KABUPATEN KEPULAUAN MENTAWAI, 2011 Implementasi Keputusan Menteri Negara Pemberdayaan Aparatur Negara Nomor 25 Tahun 2004 - , Rizky Kurniawan; , Drs. Andreas Budi Purnomo, MA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study aims to determine the index of peopleâs satisfaction with public service in the north district office sipora, knowing the correspondence between the level of the perceived interest of the service. The method used in this study is the analisis of community satisfaction index, the analisis of the level of community interest and satisfaction, and two different test avarage using the Mann-Whitney test, test using primary data and secondary data. Primary data obtained through questionnaires and direct interviews with people who've come to the Office of the District of North Sipora, while the secondary data obtained from Bappeda and the District of North Sipora. The results showed that the index of people's satisfaction with public services in the Office of the District of North Sipora still normal, and there are still differences between the degree of importance of service with the service that the community feels it is seen from many elements of service that has not been implemented properly.